Carpal Tunnel Syndrome with Wrist Trigger Caused by Hypertrophied Lumbrical Muscle and Tenosynovitis - Ayuko Shimizu; Masayoshi Ikeda; Yuka Kobayashi; Ikuo Saito; Joji Mochida (Case Reports in Orthopedics)
We present a case of carpal tunnel syndrome involving wrist trigger caused by a hypertrophied lumbrical muscle with flexor synovitis. The case was a 40-year-old male heavy manual worker complaining of numbness and pain in the median nerve area. On active flexion of the fingers, snapping was observed at the carpal area, and forceful full grip was impossible. Tinel’s sign was positive and an electromyographic study revealed conduction disturbance of the median nerve at the carpal tunnel. Magnetic resonance imaging revealed edematous lumbrical muscle with synovial proliferation around the flexor tendons. Open carpal tunnel release was performed under local anesthesia. Synovial proliferation of the flexor tendons was found and when flexing the index and middle fingers, the lumbrical muscle was drawn into the carpal tunnel with a triggering phenomenon. After releasing the carpal tunnel, the triggering phenomenon and painful numbness improved.